First data on the bionomics of Brachyodynerus magnificus magnificus (Morawitz, 1867) (Hymenoptera: Vespidae: Eumeninae) - Fateryga, Alexander V.; Ivanov, Sergey P.; Budashkin, Yury I. (Zootaxa, 2017)
Nesting of Brachyodynerus magnificus magnificus was studied in the Crimea on saline land. The nests were horizontal or inclined burrows excavated by females in lateral walls of soil cracks developed on clay ground substrate. Structure of three nests was examined; they were located in cracks 6–7 cm in depth and 0.5–1.5 cm in width; nest entrances were opened at depths of 2.5–4 cm; they were simple round openings without entrance turrets or any other structures. Two nests were abandoned by females and both had burrows 19 mm long; the third one was complete and had a burrow 33 mm long divided by transverse mud partitions onto three cells 8–10 mm long and a vestibular cell 2 mm long stopped by a final mud plug. The cells were not different from other parts of the nest burrow. Females used a liquid sucked out from succulent leaves of two halophitic plant species of the family Chenopodiaceae during nest building and did not visit any open water sources. Females hunted for caterpillars of a single species of coleophorid moth, Aporiptura ochroflava; 22–27 caterpillars were stored in each cell. Adult feeding was recorded on flowers of eight plant species, but the main nectar source was flowers of Limonium scoparium. Males spent their time feeding on flowers and searching for females at nesting and hunting sites. The species probably has two generations per year and we observed the nesting of the second generation. The distribution of the species is summarized; its presence in East Europe is confirmed. The lectotype of Odynerus magnificus Morawitz, 1867 is designated.